СКРОТАЛЬНИЙ ШКІРНИЙ МЕТАСТАЗ РЕКТАЛЬНОЇ ПЛОСКОКЛІТИННОЇ КАРЦИНОМИ: НЕЗВИЧАЙНИЙ РОЗВИТОК У РІДКІСНУ ПУХЛИНУ - Giorgi, V. De; Venturi, F.; Portelli, F.; Maida, P.; Scarfì, F.; Trane, L.; Gori, A.; Silvestri, F.; Massi, D. (PH Akademperiodyka, 2023)
Summary. The scrotum is a rare site for metastases and represents less than 1% of the body’s total surface area. Clinically, metastatic deposits in the scrotum can present in a variety of ways. They may appear as solitary cutaneous nodules, papules, plaques, or generalized induration or edema. Indeed, scrotum metastasis may be mistaken for other skin lesions since several dermatologic conditions can present with inflammation or dermatitis of the scrotum. Properly diagnosing cutaneous metastasis requires histopathological examination since the clinical appearances are, as described, highly variable and non-specific. We present a 63-year-old man with painless nodules on the scrotal skin. Excisional biopsy of the nodules revealed a metastasis from rectal squamous cell carcinoma. The incidence of this kind of tumors is estimated around 0.1–0.25 per 1000 colorectal neoplasms.